Posttranscriptional regulation of PAI-1 gene expression - Heaton, Joanne H.; Dlakic, Wendy M.; Gelehrter, Thomas D. (Thrombosis and Haemostasis, 2003)
The plasminogen activator-plasmin cascade is involved in multiple physiological and pathological processes including fibrinolysis, wound healing, fibrosis, angiogenesis, embryo implantation and tumor cell invasion and metastasis. Plasminogen activator-inhibitor type 1 (PAI-1) is the major physiological regulator of plasminogen activation. PAI-1 is expressed in a variety of mammalian cells and is regulated by growth factors, cytokines and hormones, including agents that elevate cAMP levels. Although cyclic nucleotide regulation of PAI-1 is observed in diverse cell types in various species, including human, limited studies have addressed the mechanism of this regulation. Here we review our work on the regulation of PAI-1 mRNA degradation in HTC rat hepatoma cells, describing the cis-acting cAMP-responsive sequence in the transcript and a novel RNA binding protein that interacts with it. Potential mechanisms by which this RNA-binding protein may be involved in cyclic nucleotide regulation of mRNA stability are discussed and cAMP regulation of PAI-1 in other systems is summarized.Part of this paper was originally presented at the joint meetings of the 16th International Congress of the International Society of Fibrinolysis and Proteolysis (ISFP) and the 17th International Fibrinogen Workshop of the International Fibrinogen Research Society (IFRS) held in Munich, Germany, September, 2002.
Keywords: PAI-1; mRNA decay; cyclic nucleotides; posttranscriptional regulation